2022
DOI: 10.1159/000527834
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Connections between Nonalcoholic Fatty Liver Disease and Chronic Kidney Disease

Abstract: Background: Non-alcoholic fatty liver disease and chronic kidney disease are major public health issues worldwide. The clinical burden of non-alcoholic fatty liver disease is not only confined to liver-related morbidity and mortality but it also includes the burden of chronic extrahepatic complications. It is well known that liver and kidney are strictly interconnected in physiological and pathological conditions. Summary: Mounting evidence indicates a strong association between non-alcoholic fatty liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Table 1 presents the main characteristics of the included studies. The presence of NAFLD was found to be associated with the presence of CKD in four studies [13][14][15][16] , and the development of NAFLD was found to increase the risk of CKD incidence in four additional studies [17][18][19][20] . In these eight studies [13][14][15][16][17][18][19][20] , the severity of liver disease was associated with a reduction in kidney function, regardless of known risk factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the main characteristics of the included studies. The presence of NAFLD was found to be associated with the presence of CKD in four studies [13][14][15][16] , and the development of NAFLD was found to increase the risk of CKD incidence in four additional studies [17][18][19][20] . In these eight studies [13][14][15][16][17][18][19][20] , the severity of liver disease was associated with a reduction in kidney function, regardless of known risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of NAFLD was found to be associated with the presence of CKD in four studies [13][14][15][16] , and the development of NAFLD was found to increase the risk of CKD incidence in four additional studies [17][18][19][20] . In these eight studies [13][14][15][16][17][18][19][20] , the severity of liver disease was associated with a reduction in kidney function, regardless of known risk factors. Two studies did not find an association between NAFLD and CKD nor an increase in the incidence of CKD after adjusting for metabolic syndrome elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, cross-sectional studies and one meta-analysis of cross-sectional studies have evaluated the association between NAFLD/MAFLD/MASLD and CKD, such as summarized in Table 2 [44][45][46][47][48][49][50] .…”
Section: Are Nafld/mafld/masld Associated With Ckd In Cross-sectional...mentioning
confidence: 99%
“…Studies summarized in Table 2 have yielded discrepant or conflicting findings, which probably occur owing to limited patient populations and may be explained by variable strength of association with CKD of NAFLD vs. MAFLD. Of interest, the two meta-analytic reviews by Musso et al and Agustanti et al found that NAFLD and MAFLD, respectively, were associated with a significantly higher prevalence of CKD [44,50] .…”
Section: Are Nafld/mafld/masld Associated With Ckd In Cross-sectional...mentioning
confidence: 99%